FZD5 regulates cellular senescence in human mesenchymal stem/stromal cells. (22nd December 2020) - Harada, Seiko; Mabuchi, Yo; Kohyama, Jun; Shimojo, Daisuke; Suzuki, Sadafumi; Kawamura, Yoshimi; Araki, Daisuke; Suyama, Takashi; Kajikawa, Masunori; Akazawa, Chihiro; Okano, Hideyuki; Matsuzaki, Yumi
Abstract: Human mesenchymal stem/stromal cells (hMSCs) have garnered enormous interest as a potential resource for cell-based therapies. However, the molecular mechanisms regulating senescence in hMSCs remain unclear. To elucidate these mechanisms, we performed gene expression profiling to compare clonal immature MSCs exhibiting multipotency with less potent MSCs. We found that the transcription factor Frizzled 5 ( FZD5 ) is expressed specifically in immature hMSCs. The FZD5 cell surface antigen was also highly expressed in the primary MSC fraction (LNGFR + THY-1 + ) and cultured MSCs. Treatment of cells with the FZD5 ligand WNT5A promoted their proliferation. Upon FZD5 knockdown, hMSCs exhibited markedly attenuated proliferation and differentiation ability. The observed increase in the levels of senescence markers suggested that FZD5 knockdown promotes cellular senescence by regulating the noncanonical Wnt pathway. Conversely, FZD5 overexpression delayed cell cycle arrest during the continued culture of hMSCs. These results indicated that the intrinsic activation of FZD5 plays an essential role in negatively regulating senescence in hMSCs and suggested that controlling FZD5 signaling offers the potential to regulate hMSC quality and improve the efficacy of cell-replacement therapies using hMSCs. Abstract : Although mesenchymal stem/stromal cells (MSCs) are promising for cell therapy, long-term culture leads to MSC senescence with reduced stem cell capacity. We showed that FZD5, which is specifically expressed in immature MSCs, can serve as a stemness indicator. Controlling FZD5 signaling may improve MSC quality and the outcomes of cell therapy.